Tinjauan Hukum Islam terhadap Sistem Gadai Tanah di Kecamatan Tawangmangu - Yanti, Erna, Drs. Harun M.H, Aries Indrianto, S.E.,Sy., MIFP (2016)
Pawn practice has long been applied in the Tawangmangu society. The pawn practice in rice field that occurs in the Tawangmangu society can be briefly described as follows, namely with the arrival of the A to the B intending to borrow some money to provide collateral in the form of rice field then this rice field are managed by the B to take the result until A can pay off the debt and there is no limit time in refunding the loan and sometimes to several harvest times or years. This contract can harm one party, usually those who feel most aggrieved is the pawner, because paddy land as collateral be fully utilized by the pawnee without any revenue sharing with the pawner for the harvest of the land collateral. This is presumably prompted the authors to conduct further research on the practice of paddy land in the Tawangmangu district to be discussed and analyzed in the perspective of Islamic law. The purpos of this study is to find out whether the pledge agreement executed by the Tawangmangu society in accordance with the rules of the pawn contract that have been regulated in Islamic law or not. This research is a field one, and the data obtained using the method of observation, interviews, and ocumentation. The method of data analysis is a qualitative analysis techniqu, and in the conclusion the author has used the inductive method Based on the results of the research, it is concluded that the practice of contract execution of field land pawn in district Tawangmangu is valid in accordance with the provisions of Islamic law. Regarding the full use of collateral by the pawnee is not valid because of the element making opportunistic fashion and does not maintain the values of justice and welfare.